FAKTOR - FAKTOR YANG MEMPENGARUHI DALAM MENINGKATKAN PENDAPATAN PETANI KOPI ARABIKA (Coffea arabica) DI DESA BEGANDING KECAMATAN SIMPANG EMPAT KABUPATEN KARO - Aria Sempurna Sitanggang; Juliana Br Simbolon; Rafael Remit Winardi (JURNAL REGIONOMIC, 2020)
Coffee is one of the plantations that has high economic value among other plantations crops and play an important role in the goverment. Beganding village Simpang Empat sub district Karo regency is one of the arabica coffee (Coffea arabica) producer. This aim of study is 1) to influence the vast influence of land, capital, labor, education, the experience of farmer, age and technology to the production of arabica coffee (Coffea arabica) in Beganding village Simpang Empat subdistrict Karo regency. 2) to influence the vast influence of land, capital, labor, education, the experience of farmer, age and technology and the assiciated price to boost the arabica coffee (Coffea arabica) farmer’s revenue Beganding village Simpang Empat subdistrict Karo regency. The range of this study is to examine factors that are influencing the revenue of the arabica coffee farmers in Beganding village Simpang Empat subdistrict Karo regency. The kind of data used ini the research is primary and secondary. There were 52 samples in the study and then processed using SPSS 24.00. The first experimental result 1) while the partial varibility of land and age can have a negative and significant impact on production, capital, labor, education, farmer experience, age and technology can have a positive and significant impact on production. Result of research with simultaneous of , capital, labor, education, farmer experience, age and technology can have a positive and significant impact on production. The second experimental result 2) while the partial varibility of capital and education are negative and significant to a provisonal income while land area, labor, farmer’s experience, age and technology and price have a positive and significant impact on income. Result of research with simultaneous of , capital, labor, education, farmer experience, age and technology can have a significant impact on coffee farmer income in Baganding village.